Moral pornography : towards a critique of human relations in the culture industries of art and pornography. - Yong, Faith Hui Cher. (2010)
Austria, in particular Vienna, is best known locally and internationally for being the "music city of the world". However, beneath the artificiality of Austria as the land of music and pristine beauty, lies the reality of violence in human and sexual relations. In using Theodor Adorno's theory of Culture Industry and Angela Carter's notion of moral pornography, this paper will thus examine the notion of violence in both human and sexual relations in Elfriede Jelinek's Lust and The Piano Teacher. Finally, because pornography and music have both degraded to become mere culture industries for mass consumption, I propose in this paper, that pornography in Elfriede Jelinek’s novels functions as a critique of culture industry by exposing the reality of human relations being governed by transactions, finally reducing individuals to mere objects of consumption, even in sexual relations